Actitudes hacia la política en estudiantes de la Universidad Nacional del Centro del Perú. - Cuellar Escobar, Nelfa (2023)
The ideals of the National University of Central Peru students have about politics and relationships with teachers, workers and graduates are determined. The problem was: What attitudes do students assume about politics in their daily lives? The background collection method was used, using the best-known search engines. The results demonstrate the number of articles that exist on the topic. The conclusion was that there is no scientific vision of majority acceptance and that there are positive and negative trends. The purpose was and it is to open a process of analysis and evaluation of politics and its value in social life